An organic phase transmetallation approach for synthesis of hollow Ni–Au nanocomposites with tunable cavity size. (13th November 2018) - Sardar, Debasmita; Ahmed, Md Azaharuddin; Bandyopadhyay, Sudipta; Ghosalya, Manoj Kumar; Bala, Tanushree
Abstract : Hydrophobized HAuCl4 entered Ni nanoparticles through the fractures on the surface initiating transmetallation at the centre, yielding hollow Ni–Au composites. Abstract : Ni–Au nanocomposites in the form of hollow spheres with controlled cavity size have been successfully synthesized by the transmetallation reaction between hydrophobized Ni nanoparticles and hydrophobized Au precursors. This can be considered as a fairly unique synthesis strategy that does not require any additional external reductants. The synthesis is carried out in a nonpolar solvent and precise tuning of the cavity size has been achieved only by varying the ratio of the two reacting components. A detailed characterization has been performed via UV-vis spectroscopy, XPS, TEM, EDAX, and SEM. The mechanistic aspect is established from FTIR. SQUID-VSM confirmed the magnificent superparamagnetism of the nanocomposites.